2006
DOI: 10.1002/jcb.20912
|View full text |Cite
|
Sign up to set email alerts
|

Ochnaflavone inhibits TNF‐α‐induced human VSMC proliferation via regulation of cell cycle, ERK1/2, and MMP‐9

Abstract: Ochnaflavone (c-3 of apigenin-0-c-4 of apigenin; OC), a biflavonoid present in the human diet, is known to inhibit angiotensin II-induced hypertrophy and serum-induced smooth muscle cell proliferation. OC is known to have anti-fungal and anti-inflammatory activities. However, it is not known whether OC exerts similar cardioprotective effects in cells treated with tumor necrosis factor (TNF)-alpha. In this study, we isolated OC from Lonicera japonica and studied its effect on matrix metalloproteinase-9 (MMP-9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Previous reports have shown that rhein induces apoptosis in promyelocytic leukemia HL-60 cells [24], and it is well known TNF-α-induced HASMC proliferation plays a critical role in development of vascular diseases including atherosclerosis [2,5,6,7,8,9]. However, the effect of rhein on TNF-α-induced HASMC proliferation is not well understood.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports have shown that rhein induces apoptosis in promyelocytic leukemia HL-60 cells [24], and it is well known TNF-α-induced HASMC proliferation plays a critical role in development of vascular diseases including atherosclerosis [2,5,6,7,8,9]. However, the effect of rhein on TNF-α-induced HASMC proliferation is not well understood.…”
Section: Discussionmentioning
confidence: 98%
“…Inflammatory cytokines such as TNF-α are secreted by VSMCs in the neointima after a balloon injury, as well as by macrophages in atherosclerotic lesions [33]. In addition, inflammatory cytokines also play an important role in the induction of inflammation, migration and proliferation in HASMCs [3,4,5,6,7,8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various compounds derived from natural products have been reported to modulate the growth of colorectal cancer cells and thus are considered to be cancer chemopreventive agents (Bhanot and Möller, 2009). Ochnaflavone is a natural biflavonoid and has been demonstrated to have anti-inflammatory and anti-arthreogenic activites (Lee et al, 1997;Moon et al, 2006;Son et al, 2006;Suh et al, 2006a;Suh et al, 2006b;Kim et al, 2008). Since chronic inflammation is highly correlated with colorectal carcinogenesis (Wada, 2009;Bhanot and Möller, 2009), anti-inflammatory effect of ochnaflavone might suggest its possible role in colon cancer chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological activities mediated by ochnaflavone include the inhibition of phospholipase A2 in rat platelet, lymphocyte proliferation, and arachidonate release from rat peritoneal macrophage (Chang et al, 1994;Lee et al, 1995;Lee et al, 1997). The anti-artherogenic activity of ochnaflavone was also revealed with the correlation of inhibition of human vascular smooth muscle cell proliferation induced by TNF-α via regulation of cell cycle related proteins, ERK and MMP-9 (Suh et al, 2006b). Recent study also exhibited the inhibitory activity of CCl4-induced PE degradation in rat liver microsome and anti-inflammatory effects with the downregulation of inducible nitric oxide, cyclooxygenase-2 and 5-lipoxygenase through NF-κB and ERK pathway by ochnaflavone Suh et al, 2006a).…”
Section: Introductionmentioning
confidence: 95%